Burnout in orthopaedic surgeons: a review. Issue 7 (24th June 2013) - Arora, Manit; Diwan, Ashish D.; Harris, Ian A.
Abstract Background Training and practice of orthopaedic surgery are stressful endeavours, placing orthopaedic surgeons at risk of burnout. Burnout syndrome is associated with negative outcomes for patients, institutions and, especially, the surgeon. The aim of this review is to summarize available literature on burnout among orthopaedic surgeons and provide recommendations for future work in this field. Methods A search of MEDLINE (1946–present) and EMBASE (search terms: 'Burnout, Professional' AND 'Orthopaedics'; 'Stress, Psychological' AND 'Orthopaedic Surgery'; 'Fatigue, Mental' AND 'Orthopaedic Surgery') was performed. The authors focused on articles that assessed burnout among orthopaedic surgeons. All studies used the Maslach Burnout Inventory allowing for cross‐study (and cross‐country) comparisons. Results Burnout rates among orthopaedic surgeons are in the range of 50–60%, higher than surgeons in general (range: 30–40% for surgeons in general), with the highest rate (emotional exhaustion and depersonalization scores) among orthopaedic residents, followed by department chairs, followed by faculty members. Both objective factors (caseload, practice setting, etc.) and subjective factors (perception that career was unrewarding, perception of lack of autonomy, etc.) contribute to burnout; however, subjective factors show a stronger correlation. Conclusion Despite the heavy burnout rates among orthopaedic surgeons, little work has been performed in this field. Factors responsible for burnout among various orthopaedic populations should be determined, and appropriate interventions designed to reduce burnout.